An approach to reaching the poor and disadvantaged to promote health equity in rural Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
Although the health care system has significantly expanded in the rural areas of Bangladesh duri!lg the . last two decades, the overall health status of the population has remai~ed very poor because of the uneven distribution of health and other basic services. The study asse~sed the contribution of micro credit-based health interventions in reducing the differentials in the access to arid utilization of health services and identified the specific interventions that might promote health equity. Data for this study carne from the demographic and health surveillance system of BRAC covering 70 villages in I 0 regions of the country. The surveillance system provided updated sampling frame from where a total of 3,208 households were selected at random for the survey. One adult woman from each sampled household was selected for the interviews. The survey provided basic socioeconomic information of the households, health status and access to health care and their participation in microcredit program. In-depth interviews were also conducted with key informants such as community health volunteers, local health care providers and the vulnerable individuals to assess the needs and availability of the health care services for the poor. Data were collected in September 200 I. Findings revealed significant socioeconomic differentials in the access to and the utilization of health care in the study communities. Education and landownership were strong predictors of the health service use. Gender differential in health care wa,s not significant. The access to and use of health care were much higher among the micro-credit program participants than non-participants. The health care for the poor should not only be subsidized but the mode of services must be appropriate to reach them. Subsidized treatment and medicines for the extreme poor, targeted and appropriate health services, and closer monitoring of the performance of health service providers was identified as prioritized interventions for the poor. Health services promotion at the grassroots level was costly when it was one-dimensional program. The credit-based health promotion was cost-effective since other components such as income generating activities, adult literacy and basic curative services were added to the package. The study concludes that expanded health services, integrated with poverty-focus development program, can significantly improve the access to and the utilization of health services among the poor in developing countries.